Observations on some spawning grounds of the Gangetic major carps with a note on carp seed resources in India - David, A (Indian Journal of Fisheries, 2016)
Eventhough Labeo rohita (Hamilton), Catla catla (Hamilton) and Cirrhinamrigala (Hamilton) are the three most important of the cultivable carps inthe freshwater ponds of India, definite information as to their spawningmovements and actual spawning grounds in riverine habitats is still lacking.Since these species breed in rivers and streams along with other uneconomicand predatory fishes, such knowledge is considered of primary importancefor the collection of pure quaUty of their ' spawn'—(larval stages), fry andfingerlings, which is an essential prerequisite for successful pisciculturaloperations.